6. \( \begin{aligned} 4 x-3 y & =5 \\ 6 x+2 y & =14\end{aligned} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To solve the system of equations, you can use either substitution or elimination. Here, I'll use the elimination method. First, we can multiply the first equation by 2 to align the \(y\) coefficients. This gives us: \[ \begin{aligned} 8x - 6y & = 10 \quad (1) \\ 6x + 2y & = 14 \quad (2) \end{aligned} \] Now, multiply (2) by 3 to match the coefficients of \(y\): \[ \begin{aligned} 6x + 2y & = 14 \quad \text{multiply by 3 gives} \\ 18x + 6y & = 42 \quad (3) \end{aligned} \] Next, now that we have the same coefficient of \(y\) in both equations: \[ \begin{aligned} 8x - 6y & = 10 \quad (1) \\ 18x + 6y & = 42 \quad (3) \end{aligned} \] Add (1) and (3) to eliminate \(y\): \[ 26x = 52 \] \[ x = 2 \] Substitute \(x = 2\) back into one of the original equations to find \(y\). Using the first equation: \[ 4(2) - 3y = 5 \] \[ 8 - 3y = 5 \] \[ -3y = -3 \implies y = 1 \] Thus, the solution to the system of equations is \( (2, 1) \).